Optical Coherence Tomography Angiography (OCTA) in Multiple Sclerosis and Neuromyelitis Optica Spectrum Disorder - Kleerekooper, Iris; Houston, Sarah; Dubis, Adam M.; Trip, S. Anand; Petzold, Axel (Frontiers in Neurology, 2020)
Vascular changes are increasingly recognised as important factors in the pathophysiology of neuroinflammatory disease, especially in multiple sclerosis (MS). The relatively novel technology of optical coherence tomography angiography (OCTA) images the retinal and choroidal vasculature non-invasively and in a depth-resolved manner. OCTA provides an alternative quantitative measure of retinal damage, by measuring vascular density instead of structural atrophy. Preliminary results suggest OCTA is sensitive to retinal damage in early disease stages, while also having less of a “floor-effect” compared with commonly used OCT metrics, meaning it can pick up further damage in a severely atrophied retina in later stages of disease. Furthermore, it may serve as a surrogate marker for vascular pathology in the central nervous system. Data to date consistently reveal lower densities of the retinal microvasculature in both MS and neuromyelitis optica spectrum disorder (NMOSD) compared with healthy controls, even in the absence of prior optic neuritis. Exploring the timing of vascular changes relative to structural atrophy may help answer important questions about the role of hypoperfusion in the pathophysiology of neuroinflammatory disease. Finally, qualitative characteristics of retinal microvasculature may help discriminate between different neuroinflammatory disorders. There are however still issues regarding image quality and development of standardised analysis methods before OCTA can be fully incorporated into clinical practice.